2020
DOI: 10.1002/acp.3625
|View full text |Cite
|
Sign up to set email alerts
|

How do we judge our confidence? Differential effects of meta‐memory feedback on eyewitness accuracy and confidence

Abstract: Summary According to the cue–belief model, we assess confidence in our memories using self‐credibility cues that reflect beliefs about our memory faculties. We tested the influence of meta‐memory feedback on self‐credibility cues in the context of eyewitness testimony, when feedback was provided prior to “testifying” via a memory questionnaire (Experiment 1) and after an initial memory questionnaire but before participants had to retake it (Experiment 2). Participants received feedback (good score, bad score, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This initial test mechanism may also explain why participants rarely changed their responses following negative feedback. Indeed, research suggests that feedback is likely to have a greater impact on eyewitness memory reports when a witness's memory is relatively weak than when their memory is relatively strong (Charman et al, 2010;Iida et al, 2020). Thus, completing an initial memory test may have enabled our participants to perform relatively well on leading and leading-with-feedback questions.…”
Section: Discussionmentioning
confidence: 98%
“…This initial test mechanism may also explain why participants rarely changed their responses following negative feedback. Indeed, research suggests that feedback is likely to have a greater impact on eyewitness memory reports when a witness's memory is relatively weak than when their memory is relatively strong (Charman et al, 2010;Iida et al, 2020). Thus, completing an initial memory test may have enabled our participants to perform relatively well on leading and leading-with-feedback questions.…”
Section: Discussionmentioning
confidence: 98%
“…However, during this evaluation, individuals may display tendencies of overconfidence or a lack of confidence, leading to a disparity between perceived and actual performance and affecting the accuracy of individual metacognitive monitoring ( Baranski and Petrusic 1994 ; Çapan et al 2022 ; Jackson et al 2017 ; Putnam et al 2022 ). Various factors, such as experience ( Cichoń et al 2018 ), feedback ( Iida et al 2020 ), and effort ( Lee and Daunizeau 2021 ) can affect individuals’ confidence judgments. The most important and common influencing factor is the item difficulty ( Arnold et al 2017 ; Clariana and Park 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research supports this prediction, showing that how people feel about their memory ability affects their confidence in their memory, and this effect is larger when their memory is relatively weak. For example, receiving feedback about one’s memory ability has a larger influence on confidence when internal cues are weak than when internal cues are strong (Charman et al, 2010; Iida et al, 2020). This account may explain why one previous study found that perceived memory ability did not predict accuracy or confidence when participants’ memories were tested after a short 5-min delay (Saraiva et al, 2020).…”
mentioning
confidence: 99%
“…For example, one study suggested that line-up identifications made with high confidence are likely to be, on average, highly accurate, even when eyewitness accuracy is reduced by variables outside the control of the legal system (e.g., long retention intervals; Semmler et al, 2018). But there is also evidence that some factors, such as feedback about one’s memory ability and exposure to misinformation, may impair the confidence–accuracy relationship (e.g., Flowe et al, 2019; Iida et al, 2020; Pezdek et al, 2020; Spearing & Wade, in press). One well-studied factor that is known to systematically reduce the quantity and accuracy of witnesses’ memory reports but has rarely been studied in the confidence–accuracy literature is the delay period between when a crime occurs and when a witness is asked to provide evidence (Tuckey & Brewer, 2003).…”
mentioning
confidence: 99%